Investigating the impact of oligo-chitosan on the growth dynamics and yield traits of Oryza sativa L. ‘BRRI dhan29’ under subtropical conditions - Afrina Rahman; Rayhan Ahammed; Jayanta Roy; Md Liton Mia; Mohammad Abdul Kader; Mubarak A. Khan; Md Harun Rashid; Uttam Kumer Sarker; Md Romij Uddin; Md Shafiqul Islam (Heliyon)
Reducing the harmful chemical use along with obtaining potential yield in field is a worth exploring practice in rice cultivation. To mitigate the prevailing yield gap, the current study was designed to evaluate the effect of chitosan in improving growth, yield contributing characters and yield of rice. The experiment comprised eight different treatments viz. control (no fertilizer and Chitosan) (T0), conventional method (with fertilizers) (T1), conventional method with foliar spray of 100 ppm chitosan solution (T2), conventional method with foliar spray of 300 ppm chitosan solution (T3), conventional method with foliar spray of 500 ppm chitosan solution (T4), only foliar spray of 100 ppm chitosan solution (T5), only foliar spray of 300 ppm chitosan solution (T6), and only foliar spray of 500 ppm chitosan solution (T7). The experiment was laid out in a completely randomized block design containing three replications. Data on different vegetative and yield contributing characters were recorded to evaluate the treatments effectiveness in improving rice yield. Different growth and yield contributing characters showed significant improvement after applying chitosan in addition to the conventional production system. The conventional method with foliar spray of 500 ppm chitosan solution had a greater positive effect on yield contributing characters and yield. In vegetative characters, the highest plant height became (87.3 cm), number of tiller hill−1 (13.7), Total dry matter (12.9), leaf area index (1.35), and chlorophyll content (57.73). On the basis of assessed treatments in yield contributing characters and yield, the highest plant height was (91.8 cm), no. of grains panicle−1 (145.29), grain yield (6.37 t ha−1), straw yield (6.47 t ha−1). Results showed that the conventional method with foliar spray of different concentration of chitosan solution was able to increase yield up to 26 % in comparison to the conventional method. Overall, our findings suggest that additional foliar spray of chitosan with previously recommended cultivation practice can increase the yield per unit area and offers promising technology to achieve potential yield in farmer's field.